Aktif Cegah Stunting Kelompok 43 KKM Uniba Tekankan Pentingnya Asi Eksklusif bagi Kesehatan Anak - Muhammad Rizqi Alkarom; Bahrul Alam; Sirozul Qori; Tiara Nofiana; Slamet Gunadi; Yolla Sukma Handayani; Asih Setyo Rini (Jurnal Kabar Masyarakat, 2024)
Group 43 Student Work Lectures (KKM) at Bina Bangsa University (Uniba) participated in the government's efforts to promote the prevention and reduction of stunting rates in Cilegon City. This socialization and counseling activity was carried out at the Sakinah Residence Posyandu with Midwife Lia Chaerunisah and the Head of Kalitimbang Subdistrict, M Uffan. Field Assistant Lecturer, Tiara Nofiana, emphasized that this activity really helps the community in determining the right steps for the golden growth period and cognitive development of children. The main focus of socialization is empowering stunting prevention through education regarding the importance of exclusive breastfeeding, providing appropriate MPASI, and providing nutritious food for babies and toddlers. Apart from that, the Uniba 43 KKM Group is also active in posyandu activities such as weighing babies and providing education about healthy living and the importance of nutritious food. This program received a positive response from the community and the posyandu, indicating the success of collaboration in efforts to prevent stunting in the area.